The Effect of Common Knowledge Construction Model-Based Instruction on 5th Grade Students' Conceptual Understanding of Biodiversity - Veysel Haydari; Bayram Costu (Journal of Education in Science, Environment and Health)
The aim of this study is to investigate the effect of the Common Knowledge Construction Model (CKCM) based instruction on 5th grade students’ conceptual understanding of the “biodiversity” topic. The study is conducted with 74 fifth grade female students at middle school in the district of Usküdar, Istanbul. Semi-experimental method is used. In this model, two experimental groups (Experiment 1 and Experiment 2) and a control group are randomly selected among 5th grade students. In the experiment group 1, teaching is carried out with CKCM, in the experiment group 2, CKCM supported out-of-school learning environments, and in the control group, instruction is carried out in accordance with the curriculum of Turkey. Experimental group 1 includes 24 students, 2 involves 25 students, and control group consist of 25 students. The data is collected through Biodiversity Conceptual Understanding Test (BCUT). Analyzing of BCUT data that require two-tier classification, the answers of the first tier of each question are provided by tabulating the percentages of the reasons chosen for these answers (the second tier). Which alternative concepts were chosen mostly and which ones were changed analyzed as percentage. The data collected from the students' responses to the two-tier BCUT are statistically analyzed with the help of SPSS 18.0TM. Kruskal Wallis H-Test and Wilcoxon paired pairs test are employed to analyze the data. In addition, Tamhane’s T2 test is employed from post hoc tests to determine the direction of the difference of biodiversity post-test scores. While most of the alternative concepts are remediated in experiment 1 and experiment 2 groups, in the control group it revealed that alternative concepts mostly continued. Result of the study show that CKCM is more effective in remediating alternative concepts than curriculum of the ministry of education. On the other hand, CKCM is more than curriculum of the ministry of education in terms of conceptual understanding of biodiversity. Teaching CKCM supported out-of-school learning environments do not differ in BCUT from the academic achievement only with CKCM teaching. When the post-test academic achievement of the groups is taken into consideration, a significant difference is observed between the experimental groups and the control group in favor of the experimental groups.